Direct Observation of PFIB-Induced Clustering in Precipitation-Strengthened Al Alloys by Atom Probe Tomography. (April 2022) - Tweddle, David; Johnson, Jonathan A.; Kapoor, M.; Mileski, Sean; Carsley, John E.; Thompson, Gregory B.
Abstract: Abstract : The effect of sample preparation on a pre-aged Al–Mg–Si–Cu alloy has been evaluated using atom probe tomography. Three methods of preparation were investigated: electropolishing (control), Ga + focused ion beam (FIB) milling, and Xe + plasma FIB (PFIB) milling. Ga + -based FIB preparation was shown to introduce significant amount of Ga contamination throughout the reconstructed sample (≈1.3 at%), while no Xe contamination was detected in the PFIB-prepared sample. Nevertheless, a significantly higher cluster density was observed in the Xe + PFIB-prepared sample (≈25.0 × 10 23 m −3 ) as compared to the traditionally produced electropolished sample (≈3.2 × 10 23 m −3 ) and the Ga + FIB sample (≈5.6 × 10 23 m −3 ). Hence, the absence of the ion milling species does not necessarily mean an absence of specimen preparation defects. Specifically, the FIB and PFIB-prepared samples had more Si-rich clusters as compared to electropolished samples, which is indicative of vacancy stabilization via solute clustering.